Storability and maintaining quality of banana with pretreatments by preservatives and packaging materials. (16th March 2020) - Paulos, Miilion; Ayalew, Yenenesh
Banana is the most perishable fruit crop at postharvest conditions. Thus, this experiment intended to study the effect of preservatives and packaging materials as a distinct effect and combination effect for 30 days of storage in 20°C temperature. The study consists of four post-harvest treatments (control, CaCl2, NaCl2, and tap water.) and five packaging materials (control, wooden box, plastic crate, polyethylene plastic bag, and dried banana leaf.). The effect of preservation and packaging materials observed the specific physical and chemical properties of fruit in storage conditions. Among packing materials used, wooden boxes and plastic crate showed reduced weight loss, enhanced marketability, induced TSS content and reduced decay rate. Also, CaCl2 pretreatment was maintained an enhanced physicochemical characteristics of stored banana. In complementary with distinct effect, wooden box and CaCl2 combination shown positive contributions on storage quality maintenance in most parameters. Therefore, the study demonstrated plastic crate packaging, wooden box and calcium chloride treatments of fruit resulted in longer storability and maintained the qualities of fruit.